2015
DOI: 10.1590/0103-9016-2014-0094
|View full text |Cite
|
Sign up to set email alerts
|

Use of organic compost produced from slaughterhouse waste as fertilizer in soybean and corn crops

Abstract: Slaughterhouses generate large amounts of rumen content and its use as a fertilizer may offer an environmentally friendly strategy for its management. The effect of an organic fertilizer produced from slaughterhouse waste on the fertility of sandy and clayey soils as well as soybean yield (Glycine max L.) and corn (Zea mays L.) crops was evaluated. Field experiments were set up and five rates up to 16 t ha −1 of organic fertilizer (293 kg ha −1 N, 334 kg ha −1 P and 27 kg ha −1 K) were applied annually, before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…This is due to the content of the desired nutrients in this organic fertilizer and the possibility of supplying organic matter to the soil. Similar studies using compost from slaughter waste for soybean and maize cultivation were conducted by Nunes et al (2015). Mandal et al (2013) found that composted poultry manure contributes to the improvement of physical and chemical properties of soil.…”
Section: Resultsmentioning
confidence: 61%
“…This is due to the content of the desired nutrients in this organic fertilizer and the possibility of supplying organic matter to the soil. Similar studies using compost from slaughter waste for soybean and maize cultivation were conducted by Nunes et al (2015). Mandal et al (2013) found that composted poultry manure contributes to the improvement of physical and chemical properties of soil.…”
Section: Resultsmentioning
confidence: 61%
“…2F). Among the main problems associated with the use of organic sources, such as slaughterhouse residues, as substitutes of commercial fertilizers applied to crops is the need for high dosages of residues (Nunes et al, 2015), usually occurring in tons. Due to the high N content of the alternative HHF source (12.4%), high dosage was not required to obtain a productivity result similar to urea, making it feasible for soil application.…”
Section: Discussionmentioning
confidence: 99%
“…A aplicação contínua de compostos orgânicos, pode proporcionar o efeito cumulativo de nutrientes no solo, havendo a possibilidade de diminuição nas taxas de aplicações necessárias para alcançar os máximos rendimentos (Nunes et al, 2015;Borges et al, 2012). Em trabalho realizado por , com a cultura do milho em função do efeito residual da adubação organomineral em cultivo de segundo ano consecutivo, verificaram que a adubação organomineral promoveu interações benéficas como melhoria na estrutura química e física do solo, resultando no fornecimento de nutrientes as plantas de milho.…”
Section: Introductionunclassified